The morphology and morphosyntax of the personal pronouns in the Amqi-Amarna letters - Westhuizen, J. P. van der (Journal for semitics, 2007)
This paper is concerned with the morphology and the morphosyntax of the personal pronouns, independent and suffixed, as they appear and function in the Amqi-Amarna letters. The difference as well as the correspondence in form, compared to the standard Akkadian pronouns, as also WS influences are pointed out. This is illustrated through the fact that though the Akkadian pronouns, both independent and suffixed, can be divided into three distinct morphological groups, viz. 1) nominative; 2) oblique (accusative and genitive); and 3) dative, not all of these pronouns function in the Amqi letters. This is followed by an investigation of the different syntagmas in which these pronouns function and the cases where the independent pronouns are used in conjunction with prepositions. Cases where the nominative function either as the subject (topic) or predicate (comment) as well as cases of extraposition are also discussed.